Review of the Stepwise Laboratory Quality Improvement Process Towards Accreditation (SLIPTA) version 2:2015 - Tjeerd A.M. Datema; Linda Oskam; Jacqueline E.W. Broerse; Paul R. Klatser (AOSIS, 2020)
Background: In 2011 the Stepwise Laboratory Quality Improvement Process Towards Accreditation (SLIPTA) was launched, aimed at strengthening the quality and competence of African clinical, public health and reference laboratories. We reviewed the first version of the SLIPTA checklist in 2011. The continued development and publication of a new version of the International Organization for Standardization (ISO) 15189 standard demands a renewed review. Objective: This study aimed to determine the suitability of SLIPTA in guiding laboratories towards ISO 15189:2012 compliance and accreditation and provide recommendations for further SLIPTA improvement. Methods: The study was conducted between September 2018 and April 2019. Coverage of ISO 15189:2012 by SLIPTA checklist version 2:2015 was determined and the point distribution of the scoring system over the different sections of the SLIPTA checklist was re-investigated. These findings were compared with the review of the first version of the SLIPTA checklist (based on ISO 15189:2007) and with findings published on SLIPTA implementation and roll-out. Results: The coverage of ISO 15189 by the SLIPTA checklist has increased, even though ISO 15189:012 is more extensive than ISO 15189:2007. The point distribution is still skewed towards sections related to quality planning rather than quality control and improvement. Although to date 314 laboratories have been assessed, barriers for laboratories to participate in SLIPTA are high. Sustainability of SLIPTA results is insufficiently studied. Conclusion: SLIPTA checklist version 2:2015 has improved compared to earlier versions. We recommend increasing accessibility for laboratories to participate and increasing guidance for ISO-based quality management system implementation.